Variables Affecting the Risk of Vehicle Collisions in Australian Road Tunnels - Edwin Hidayat; David Lange; Jurij Karlovsek; Jiwon Kim (Journal of Road Safety)
The characteristics of road tunnels as part of the road network differ from those of general open roads, resulting in different vehicle collision characteristics. Understanding the characteristics of these collisions and the variables that contribute to them is critical for developing mitigation strategies. The purpose of this paper is to identify the characteristics of vehicle collisions in Australian road tunnels, as well as to investigate the variables that influence the number of casualties and the types of collisions. The study utilised data from seven road tunnels in Queensland and New South Wales. Data cleaning and transformation were carried out, yielding 12 variables for further analysis with statistical descriptive analysis, cross-tabulation, and logistic regression. The findings reveal that rear-end collisions are the most common type of collision in Australian road tunnels. Furthermore, only one variable had a significant impact on the number of casualties, while three variables had a significant impact on the types of collisions. These findings provide valuable insights for tunnel stakeholders in developing preventive measures to improve road tunnel safety.